Reviewing Elementary School Students'Vocabulary through Paper Airplane Game - Mutia Okselina; Desvalini Anwar (Universitas Negeri Padang, 2018)
This paper’s aim is to explain how to use paper airplane game in reviewing students’ vocabulary. Elementary school students’ vocabulary (in knowing and understanding the vocabulary) relatively average because of some factors that are lacks of motivation and the use of inappropriate way of teaching in the classroom. Paper airplane game is one of the way of teaching that can be used by the teacher to overcome the problems. Paper airplane game helps students to improve their vocabulary comprehension that have been learned before. The steps in using paper airplane game are brainstorming, discussing about the material, and playing the paper airplane game. In brainstorming, teacher shows several pictures related to the material along with general questions about the pictures after that. The next step is discussing about the material, teacher will put the students in-group and they will discuss about the material guide by the questions given by the teacher. The next step is playing paper airplane game, teacher will guide the students in playing this game that will help them in improving the vocabulary that has been taught. And the last steps is concluding. In this step, the teacher make the conclusion about the material.